2005
DOI: 10.1007/s10943-004-1146-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgeons and the Spirit: A Study on the Relationship of Religiosity to Clinical Practice

Abstract: This study aimed to identify the religious practices and beliefs of surgeons and the relationship between surgeons' locus of control and religiosity. Thirty-five surgeons completed a survey that included items from the Duke University Religion Index, the Salesian Center Intrinsic Religiosity Scale for Clinicians, and Rotter's Locus of Control Scale. Over 68% of sampled surgeons affirmed that their religious beliefs play a part in their practice, 47% attend religious services at least weekly, and 44% pray daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Among paediatric oncologists from the US, half of them assumed that their spiritual/religious beliefs influence the interactions with patients and colleagues [22]. A smaller study enrolling 53 US surgeons found that their “religious beliefs play a part” in their clinical practice, that they feel “guided by a higher power than my own abilities” in their practice, and that their religious beliefs were helpful to deal with their “inability to heal patients with poor prognoses” [23]. In a sample of German psychiatrists, 54% stated that “Religious beliefs influence whole approach to life,” 37% of them tried to “carry religion into other aspects of life,” and also 36% “experience God's presence” [24].…”
Section: Introductionmentioning
confidence: 99%
“…Among paediatric oncologists from the US, half of them assumed that their spiritual/religious beliefs influence the interactions with patients and colleagues [22]. A smaller study enrolling 53 US surgeons found that their “religious beliefs play a part” in their clinical practice, that they feel “guided by a higher power than my own abilities” in their practice, and that their religious beliefs were helpful to deal with their “inability to heal patients with poor prognoses” [23]. In a sample of German psychiatrists, 54% stated that “Religious beliefs influence whole approach to life,” 37% of them tried to “carry religion into other aspects of life,” and also 36% “experience God's presence” [24].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 This is the first international study of GOs' R/S beliefs. This survey suggests that many GOs use R/S beliefs to cope, like the patients do.…”
Section: Discussionmentioning
confidence: 99%
“…10 A survey of surgeons found that 68% felt that their R/S beliefs played a role in their medical practice. 11 One might expect that the stronger a physician's R/S beliefs, the more likely they would be to assess patients' beliefs. In fact, a large, cross-sectional survey of US physicians who self-identified as R/S showed that they were more likely to address R/S beliefs clinically.…”
mentioning
confidence: 99%
“…Responses are scored such that low scores indicate high religiosity; therefore, responses were reverse scored so that high levels equal high religiosity. The DUREL has demonstrated high reliability (Cronbach's alpha 5 .89; Cheever et al, 2005).…”
Section: Methodsmentioning
confidence: 99%